Screening of Neutralizing Antibodies against FaeG Protein of Enterotoxigenic Escherichia coli - Yang Tian; Sijia Lu; Saisai Zhou; Zhen Li; Shuaiyin Guan; Huanchun Chen; Yunfeng Song (Veterinary Sciences)
The misuse of antibiotics in veterinary medicine presents significant challenges, highlighting the need for alternative therapeutic approaches such as antibody drugs. Therefore, it is necessary to explore the application of antibody drugs in veterinary settings to reduce economic losses and health risks. This study focused on targeting the F4ac subtype of the FaeG protein, a key adhesion factor in enterotoxigenic Escherichia coli (ETEC) infections in piglets. By utilizing formaldehyde-inactivated ETEC and a soluble recombinant FaeG (rFaeG) protein, an antibody library against the FaeG protein was established. The integration of fluorescence-activated cell sorting (FACS) and a eukaryotic expression vector containing murine IgG Fc fragments facilitated the screening of anti-rFaeG IgG monoclonal antibodies (mAbs). The results demonstrate that the variable regions of the screened antibodies could inhibit K88-type ETEC adhesion to IPEC-J2 cells. Furthermore, in vivo neutralization assays in mice showed a significant increase in survival rates and a reduction in intestinal inflammation. This research underscores the potential of antibody-based interventions in veterinary medicine, emphasizing the importance of further exploration in this field to address antibiotic resistance and improve animal health outcomes.